A Review on the Control Parameters of Natural Convection in Different Shaped Cavities with and without Nanofluid - Rostami, Sara; Aghakhani, Saeed; Pordanjani, Ahmad Hajatzadeh; Afrand, Masoud; Cheraghian, Goshtasp; Öztop, Hakan Fehmi E.; Shadloo, Mostafa Safdari (Mdpi, 2020)
Natural convection in cavities is an interesting subject for many researchers. Especially, in recent years, the number of articles written in this regard has grown enormously. This work provides a review of recent natural convection studies. At first, experimental studies were reviewed and, then, numerical studies were examined. Then, the articles were classified based on effective parameters. In each section, numerical studies were examined the parameters added to the cavity such as magnetic forces, fin, porous media and cavity angles. Moreover, studies on non-rectangular cavities were investigated. Free convection in enclosures depends more on the fluid velocity relative to the forced convection, leading to the opposite effect of some parameters that should essentially enhance rate of heat transfer. Nanoparticle addition, magnetic fields, fins, and porous media may increase forced convection. However, they can reduce free convection due to the reduction in fluid velocity. Thus, these parameters need more precision and sometimes need the optimization of effective parameters.
Keywords: natural convection; cavity; numerical study; nanofluid; non-Newtonian